The Perfect Neighbor (A Jessie Hunt Psychological Suspense Thriller-Book Nine) - Blake, Pierce (Lukeman Literary, 2020)
"A masterpiece of thriller and mystery. Blake Pierce did a magnificent job developing characters with a psychological side so well described that we feel inside their minds, follow their fears and cheer for their success. Full of twists, this book will keep you awake until the turn of the last page." --Books and Movie Reviews, Roberto Mattos (re Once Gone) THE PERFECT NEIGHBOR is book #9 in a new psychological suspense series by bestselling author Blake Pierce, which begins with The Perfect Wife, a #1 bestseller (and free download) with nearly 500 five-star reviews. In an exclusive and wealthy neighborhood in Manhattan Beach, a new neighbor moves into a luxury home-only to be found dead soon thereafter. The case brings Jessie into another wealthy beach town, evoking bad memories of her marriage and forcing her to confront her own demons-while trying to unmask the lies of this seemingly perfect town. Was the murder connected to an exclusive party for the elite? Or is there an even more nefarious motive at stake? Making matters worse, Jessie's husband is now out of prison-and a potential threat to her once more. A fast-paced psychological suspense thriller with unforgettable characters and heart-pounding suspense, THE PERFECT NEIGHBOR is book #9 in a riveting new series that will leave you turning pages late into the night.
Keywords: Dobrodružství, napětí, thrillery; Krimi, detektivky